2005
DOI: 10.3748/wjg.v11.i12.1843
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone mineral density and altered bone turnover markers in patients with non-cirrhotic chronic hepatitis B or C infection

Abstract: AIM: Previous studies suggest that loss of bone mineral density (BMD) frequently occurs in patients with chronic viral liver disease, presenting with histologically proven liver cirrhosis. However, little is known about the occurrence of bone disease in non-cirrhotic patients with chronic hepatitis B or C. Therefore, it was the aim of this study to evaluate this particular population for BMD and bone turnover markers. METHODS:Biochemical markers of bone turnover and BMD were measured in 43 consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
91
3
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 32 publications
13
91
3
3
Order By: Relevance
“…Patients (especially males) with detectable HCV RNA expressed low BMD (at LS and hip), also in accordance with other studies [35,36]. No correlations were found between fibrosis grade and low BMD, a finding in accordance with some authors [30,37] but different from other studies [38]. Furthermore, we demonstrated that antiviral treatment, especially peginterferon alpha 2a and ribavirin, represents a risk factor for low BMD at all sites scans.…”
Section: Discussionsupporting
confidence: 75%
“…Patients (especially males) with detectable HCV RNA expressed low BMD (at LS and hip), also in accordance with other studies [35,36]. No correlations were found between fibrosis grade and low BMD, a finding in accordance with some authors [30,37] but different from other studies [38]. Furthermore, we demonstrated that antiviral treatment, especially peginterferon alpha 2a and ribavirin, represents a risk factor for low BMD at all sites scans.…”
Section: Discussionsupporting
confidence: 75%
“…Hypogonadism, abnormalities of vitamin D metabolism, and increased bilirubin levels, situations usually found in chronic liver disease, may lead to either reduced bone formation or increased bone resorption [23][24][25]. The results from the studies that have investigated the impact of hepatitis C on osteoporosis of hemophilia patients are conflicting.…”
Section: Discussionmentioning
confidence: 76%
“…Osteoporosis is a frequent complication of end-stage liver disease irrespective of its etiology. The prevalence varies between 9% and 60%, the highest being observed in cholestatic disorders and alcoholic liver disease [23] . The present study aimed at elucidating the influence of bilharziasis, hepatitis B or C infections on the development of osteoporosis in children.…”
Section: Discussionmentioning
confidence: 99%